PROBLEMATIKA SISTEM PENDIDIKAN ISLAM DI NEGARA ISLAM - Dandy Sobron Muhyiddin; Abdul Raup; Izzuddin Musthafa; Hisny Fajrussalam (Taklim : Jurnal Pendidikan Agama Islam, 2021)
This article will try to explore the thoughts of Dr. Majid 'Irsan al-Kailani is concerned with Islamic education in the Islamic world. The research method used is content analysis with a qualitative approach. The primary data used is the Manāhij al-Tarbiyyah al-Islāmiyyah al-Murabbūna al-‘Āmilūna Fīhā book by Dr. Majid 'Irsan al-Kailani in Chapter I on the Islamic Education System in Islamic Countries. Meanwhile, secondary data were obtained from books and journal articles related to the Islamic education system. The results of the study show that the curriculum as an educational system implemented in Islamic countries is divided into 2 (two) namely the paternalistic curriculum and the curriculum that escapes social reality. The educational curriculum in the Islamic world has in fact implemented many educational patterns that imitate the Western world, even though not all Western-style education systems are in accordance with the culture and value system of Islamic society..Keywords: Islamic Education; Thoughts; Curriculum